2006
DOI: 10.1007/s11172-006-0436-3
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of thiols and organic disulfides with iron and its oxides

Abstract: The influence of O 2 and H 2 O on the formation of iron dithiolates (IDTs) by the reactions of thiols and organic disulfides with the iron powder was studied under the static (without mechanical activation of the reaction) and dynamic (with mechanical activation of the reac tion) conditions. Under the static conditions in the absence of O 2 or H 2 O, only BnSH and PhSH give IDTs, whereas DdSH (Dd is dodecyl) produces IDTs in the presence of O 2 or H 2 O. For the mechanical activation of the reactions of organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In the previous work, 3 we have shown that in the reaction with the powder of reduced iron thiols 1d,e form iron dithiolates (IDT) at room temperature, and thiol 1e exceeds thiol 1d in reactivity, which is undoubtedly re lated to a higher acidity of thiol 1e compared to thiol 1d. It is found in the present work that these thiols, when reduced with hydrogen, form mostly H 2 S (cf.…”
Section: Resultsmentioning
confidence: 98%
“…In the previous work, 3 we have shown that in the reaction with the powder of reduced iron thiols 1d,e form iron dithiolates (IDT) at room temperature, and thiol 1e exceeds thiol 1d in reactivity, which is undoubtedly re lated to a higher acidity of thiol 1e compared to thiol 1d. It is found in the present work that these thiols, when reduced with hydrogen, form mostly H 2 S (cf.…”
Section: Resultsmentioning
confidence: 98%
“…(3) The formation of ferrous dithiolates was not observed upon mechanochemical activation of the reaction between organic disulfides and metallic iron [4,5].…”
Section: Resultsmentioning
confidence: 99%
“…The formation of Fe(SDd) 2 was identified by the color reaction for ferrous dithiolates containing n-alkyl or benzyl radicals. In this reaction, the brown color due to Fe(SDd) 2 changes into green upon contact with dioxygen [4,5].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations